2016
DOI: 10.1016/j.chemosphere.2016.06.094
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and reliable technique for N -nitrosodimethylamine analysis in reclaimed water by HPLC-photochemical reaction-chemiluminescence

Abstract: Kodamatani, H. (2016). A rapid and reliable technique for Nnitrosodimethylamine analysis in reclaimed water by HPLC-photochemical reaction-chemiluminescence. Chemosphere, 161 104-111. A rapid and reliable technique for N-nitrosodimethylamine analysis in reclaimed water by HPLC-photochemical reaction-chemiluminescence AbstractA fast and reliable analytical technique was evaluated and validated for determination of Nnitrosodimethylamine (NDMA) formation and rejection by reverse osmosis (RO) membranes in potable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…There is no uniform standard method, which can quickly and accurately determine ng/L concentration NDMA. The existing methods can only rely on new instruments or related accessories to achieve the accuracy of detection [133][134][135][136][137]. The operation is complicated and not cost-effective.…”
Section: Monitoring Methodsmentioning
confidence: 99%
“…There is no uniform standard method, which can quickly and accurately determine ng/L concentration NDMA. The existing methods can only rely on new instruments or related accessories to achieve the accuracy of detection [133][134][135][136][137]. The operation is complicated and not cost-effective.…”
Section: Monitoring Methodsmentioning
confidence: 99%
“…Concentrations of NDMA were analyzed and determined using a high-performance liquid chromatography-inline anion exchange reaction-photochemical reaction-chemiluminescence (HPLC-AEM-PR-CL) [38,39]. The description below was adopted from [40] for a concise explanation of the applied analytical technique:…”
Section: Ndma Analysismentioning
confidence: 99%
“…Prior studies have demonstrated the accuracy of the HPLC-PR-CL method for NDMA analysis in waters. 18,19 In the present study, an online adaptation of the instrument was 154 validated for UF-treated wastewater. The sampling system consisted of a 200 mL beaker 155 holding UF-treated wastewater, a magnetic stirrer, a peristaltic pump and 6 mm i.d.…”
Section: Validation Protocolmentioning
confidence: 99%
“…HPLC-PR-CL for NDMA analysis has been validated in prior work including comparison with a conventional method (solid phase extraction followed by GC-MS/MS) and evaluation of interference by common process chemicals (monochloramine, hydrogen peroxide and hypochlorite) and organic compounds in treated wastewaters. 18 Among the process chemicals, 93 only hypochlorite interfered with NDMA analysis but the interference was eliminated by 94 dosing a reducing agent, which is a standard procedure for NDMA analysis to prevent 95 NDMA formation in the sample bottle prior to analysis. Interference from organic 96 constituents in secondary and ultrafiltration (UF)-treated wastewaters was also avoided by 97 reducing the sample injection volume, while no interference was identified with RO 98 permeate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation